Influence Pattern Foster People Old And Attitude Language To Reading Ability Understanding - ., Sam Hermansyah; Hambing, Agus; Dirga Mubaroq, Muh (La Ogi : English Language Journal, 2024)
This study aims to determine (1) the influence of parents' parenting styles and language attitudes collectively on reading comprehension abilities; and (2) the influence of parents' parenting styles and language attitudes individually on reading comprehension abilities. This research employs a quantitative approach with a descriptive method. Data collection was conducted using questionnaires and objective tests. Questionnaires were used to gather data on parents' parenting styles and language attitudes, while objective tests were used to collect data on reading comprehension abilities. The sample for this study consisted of 69 students. Data analysis was conducted using descriptive statistics and regression analysis techniques. The results of the study indicate that (1) there is a positive and significant influence of parents' parenting styles and language attitudes collectively on the reading comprehension abilities of seventh-grade students at SMP Negeri 1 Maiwa, amounting to 85.5%; and (2) there is a positive and significant influence of parenting styles on reading comprehension abilities amounting to 38.7%, and the influence of language attitudes on reading comprehension abilities is 10.2%. These findings suggest that both good parenting styles and positive language attitudes contribute significantly to students' reading comprehension abilities. Parenting styles provide a greater contribution compared to language attitudes in enhancing students' reading comprehension skills.